A Direct Digital Synthesis Transmitter for 5G Applications With Low-Resolution DACs - Chang, Yu-Chen; Chen, You-Huei; Chen, Jau-Horng; Chen, Yi-Jan Emery (IEEE transactions on circuits and systems. II, Express briefs, 2024)
Conventional radio frequency (RF) transmitters frequently necessitate a pair of high-resolution, high-speed digital-to-analog converters (DACs) to ensure a specific level of linearity in wireless communication systems. Nevertheless, the high-resolution DACs escalate power consumption and area requirements and intensify the need for heat dissipation mechanisms. This brief presents a direct digital synthesis (DDS) transmitter using a pair of RF DACs with just 2 bits of resolution. The DDS transmitter, which uses a proposed digital pulse-width modulation signal with dithering, is resistant to power amplifier (PA) nonlinearity. Tested with 5G uplink signals and a pair of nonlinear PAs at 836.5 MHz, the transmitter could pass the stringent spectral requirements for 5G applications without using any digital predistortion or calibration techniques.